Obeloi and iron in archaic Greece - Haarer, P; Haarer, Peter (2000)
﻿ This thesis studies spits and iron in Archaic Greece and Cyprus. Chapter One surveys previous research on spits and iron. Chapters Two to Six consider the evidence for spits in detail with the following agenda: who used them, when, where, for what, how, and what were their associations? Chapters Two, Three and Four focus on archaeological finds from funerary, settlement and sanctuary contexts respectively. Chapter Five looks at the iconographic evidence, and Chapter Six deals with written references to spits in inscriptions and literary texts. Throughout these chapters, the ancient tradition that spits were used as a favoured form of pre-coinage money is considered carefully. It is concluded that the material evidence fails to support this interpretation, and that the tradition was invented in the fourth century. Nevertheless, denominations of coins were named after spits, and it is hypothesised that this resulted from the appropriation of spits and bundles of spits as visual analogies with which to describe the relationship between obols and drachmas. Chapter Seven observes that in Aegean Greece and Cyprus, metal spits were manufactured exclusively from iron from the tenth /ninth century onwards. Moreover, they were one of the largest of a range of new iron types to be introduced during the Early Iron Age, were manufactured from high quality metal, and were a long-lived type. As such, they offer an "index" of the value of iron. Chapter Eight uses this index to argue that, contrary to established views, the high Late Bronze Age value of iron persisted into the tenth century, and though it declined thereafter, it did so gradually. Moreover, iron did not become a cheap alternative to bronze. These conclusions have important ramifications for the interpretation of the transition from bronze to iron. Chapter Nine provides a brief summary of the thesis.